The fate of Atlantic Water heat in the Arctic Ocean - Richards, A (2022)
Atlantic Water (AW) is the most significant source of oceanic heat in the Arctic Ocean, and has played a key role in recent Arctic sea ice loss. Better understanding of the spatial and temporal variability of AW heat and its future evolution is therefore key to understanding future Arctic change.